1997
DOI: 10.1530/eje.0.1370240
|View full text |Cite
|
Sign up to set email alerts
|

Increased fracture frequency in adult patients with hypopituitarism and GH deficiency

Abstract: Fracture frequency was studied in 107 hypopituitary patients with GH deficiency (GHD) (69 men, mean age 53 years, range 18-74 and 38 women, mean age 54 years, range 31-73). Routine hormonal replacement therapy was given, except GH. Five male patients and 15 female patients with untreated hypogonadism were allocated to a separate group. The mean duration of hypopituitarism was 13.4 years. The prevalence of a history of fractures was assessed using questionnaires. A subsample of the Göteborg WHO MONICA Project w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
2
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(150 citation statements)
references
References 23 publications
(20 reference statements)
5
137
2
6
Order By: Relevance
“…Rosen et al (35) showed a threefold increase in fracture rate in hypopituitary patients from a single centre compared with a group of mixed European population (the MONICA project). The odds ratios for fracture frequency were 3.97 and 2.64 in men and women respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Rosen et al (35) showed a threefold increase in fracture rate in hypopituitary patients from a single centre compared with a group of mixed European population (the MONICA project). The odds ratios for fracture frequency were 3.97 and 2.64 in men and women respectively.…”
Section: Discussionmentioning
confidence: 99%
“…GHD is associated with decreased bone mineral density (BMD) in GHD children, COGHD adults and AOGHD adults, reflecting decreased bone accretion and/or reduced bone turnover (reviewed by Monson et al 2002, Verhelst & Abs 2002. The reduced BMD in AOGHD is associated with an increased incidence of fractures, particularly in men (Rosen et al 1997). Osteoporosis is similarly prevalent in untreated GH-resistant LS patients (Laron 2001).…”
Section: Body Compositionmentioning
confidence: 99%
“…Pacientes com deficiência de GH têm redução na DMO e risco aumentado de fraturas, associados a diminuição do processo de remodelação óssea (47,48). Três de nossos pacientes tiveram diagnóstico de osteoporose na avaliação basal e 27 tiveram diagnóstico de osteopenia, ou seja, 43% dos pacientes apresentavam algum grau de redução de DMO com conseqüente aumento no risco de fraturas, sendo a maioria com deficiência de GH de início na infância.…”
Section: Deficiência De Gh Em Adultos: Estudo Brasileirounclassified